Nucleic acid vaccines: innovations, efficacy, and applications in at-risk populations - Konopka, Emily N.; Edgerton, Arden O.; Kutzler, Michele A. (Frontiers in Immunology, 2025)
For more than two centuries, the field of vaccine development has progressed through the adaptation of novel platforms in parallel with technological developments. Building off the advantages and shortcomings of first and second-generation vaccine platforms, the advent of third-generation nucleic acid vaccines has enabled new approaches to tackle emerging infectious diseases, cancers, and pathogens where vaccines remain unavailable. Unlike traditional vaccine platforms, nucleic acid vaccines offer several new advantages, including their lower cost and rapid production, which was widely demonstrated during the COVID-19 pandemic. Beyond production, DNA and mRNA vaccines can elicit unique and targeted responses through specialized design and delivery approaches. Considering the growth of nucleic acid vaccine research over the past two decades, the evaluation of their efficacy in at-risk populations is paramount for refining and improving vaccine design. Importantly, the aging population represents a significant portion of individuals highly susceptible to infection and disease. This review seeks to outline the major impairments in vaccine-induced responses due to aging that may be targeted for improvement with design and delivery components encompassing mRNA and DNA vaccine formulations. Results of pre-clinical and clinical applications of these vaccines in aged animal models and humans will also be evaluated to outline current successes and limitations observed in these platforms.